HUBUNGAN ANTARA SKOR IPSS DAN SKOR IIEF PADA PASIEN BPH DENGAN GEJALA LUTS YANG BEROBAT DI POLI BEDAH RSUP PROF. DR. R. D. KANDOU MANADO - Asalia, Margali; Monoarfa, Richard; Lampus, Harsali F. (Universitas Sam Ratulangi, 2015)
Abstract: Lower urinary tract symptoms (LUTS) due to benign prostatic hyperplasia (BPH) are common in elderly men. In addition to LUTS, patients with BPH also often experience erectile dysfunction (ED). According to the data obtained from 30 BPH patients with symptoms of LUTS using the international prostate symptoms score (IPSS), 53.3% had symptoms of LUTS with a severe degree, and based on the international index of erectile function (IIEF), BPH patients with LUTS symptoms and ED were found to have erectile function (EF) as much as 26.7% with a mild and severe degree, orgasmic function (OF) as much as 40% with a severe degree, sexual intercourse function (SI) as much as 46.7% with a mild-to-moderate degree, sexual satisfaction (SS) as much as 33.3% with a severe degree and overall satisfaction (OS) as much as 43.3% with a mild degree. In this study, the investigators wanted to examine the relationship between the IPSS with the IIEF scores in BPH patients with symptoms of LUTS in the outpatient surgery department of Prof. Dr R. D. Kandou General Hospital Manado. Based on the results of the spearman correlation test, relationship between the IPSS with the IIEF score yielded EF (R: 0.372), OF (R: 389), SI (R: 0.129), SS (R: 0.351), OS (R: 0, 84). These results suggest the presence of a relationship between IPSS and IIEF scores.Keywords: IPSS, IIEF, LUTS, BPHAbstrak: Lower urinary tract symptoms (LUTS) yang disebabkan oleh benign prostatic hyperplasia (BPH) merupakan suatu kondisi yang sering terjadi pada pria usia lanjut. Selain gejala LUTS, pasien BPH sering juga disertai dengan disfungsi ereksi (DE). Menurut data yang diperoleh dari 30 pasien BPH dengan gejala LUTS dengan menggunakan International prostate symptoms score (IPSS) didapatkan 53,3% mengalami gejala LUTS dengan derajat berat dan pasien BPH dengan gejala LUTS yang mengalami DE dengan menggunakan skor international index of erectile function (IIEF) ditemukan fungsi ereksi (FE) sebanyak 26,7% dengan derajat ringan dan berat, fungsi orgasme (FO) sebanyak 40% dengan derajat berat, hubungan seksual (HS) sebanyak 46,7% dengan derajat Ringan-sedang, kepuasan seksual (KS) sebanyak 33,3% dengan derajat berat dan kepuasan menyeluruh (KM) sebanyak 43,3% dengan derajat ringan. Dengan melakukan penelitian ini, peneliti ingin mengetahui hubungan antara skor IPSS dengan skor IIEF pada pasien BPH dengan gejala LUTS di poli Bedah RSUP Prof. Dr. R. D. Kandou Manado. Berdasarkan hasil uji kolerasi menggunakan spearman untuk mengetahui hubungan antara skor IPSS dengan skor IIEF didapatkan FE (R:0,372), FO (R: 389), HS (R:0,129), KS (R: 0,351), KM (R: 0,84). Dari hasil tersebut dapat dilihat adanya hubungan antara skor IPSS dan skor IIEF.Kata kunci: IPSS, IIEF, LUTS, BPH